Unveiling Value: Intellectual Capital Disclosure, Financial Performance, and Market Capitalization: Mengungkap Nilai: Pengungkapan Modal Intelektual, Kinerja Keuangan, dan Kapitalisasi Pasar - Sigit Hermawan; Eva Eva (Universitas Muhammadiyah Sidoarjo, 2021)
This study investigates the interplay between intellectual capital disclosure, financial performance (measured through ROA, ROE, and EPS), and market capitalization within the context of Indonesian financial and telecommunications firms listed on the stock exchange during 2012-2016. Employing a quantitative approach, the research analyzes secondary data from annual reports. By applying classical assumption testing and multiple linear regression, the findings reveal a significant positive influence of intellectual capital disclosure on both market capitalization and financial performance indicators. This underscores the critical role of intellectual capital in shaping market valuation and financial success, offering valuable insights for practitioners, policymakers, and researchers delving into corporate disclosure strategies and their far-reaching ramifications.Highlight: Interplay of Intellectual Capital: Investigates the relationship between intellectual capital disclosure, financial performance metrics (ROA, ROE, EPS), and market capitalization in Indonesian financial and telecommunications firms during 2012-2016. Data-Driven Analysis: Utilizes a quantitative approach involving secondary data from annual reports, employing classical assumption testing and multiple linear regression to draw meaningful insights. Significant Influence: Demonstrates a substantial positive impact of intellectual capital disclosure on both market capitalization and financial performance, underscoring its pivotal role in shaping market valuation and overall business success. Keyword: Intellectual Capital Disclosure, Financial Performance, Market Capitalization, Quantitative Analysis, Corporate Disclosure Strategies.